Assessment of Vocabulary Development in Preschool Children Using Peabody Picture Vocabulary Test-4 - Arshad, Tafseela; Khan, Muhammad Azzam; Imtiaz, Rooma; Ramzan, Hina; Tanveer, Muhammad; Ashraf, Anum (Indus Journal of Bioscience Research, 2025)
Background: Receptive vocabulary plays a crucial role in early language development and literacy skills. The Peabody Picture Vocabulary Test-4 (PPVT-4) is a standardized tool for assessing receptive vocabulary, but its applicability in non-native English-speaking populations, such as Pakistani preschoolers, remains underexplored. Objective: To assess receptive English vocabulary development in preschool children aged 3–5 years using the PPVT-4 and determine whether their vocabulary skills align with age expectations. Methods: A cross-sectional study was conducted on 278 preschool children from four private schools in Lahore, Pakistan. The PPVT-4 was administered individually to assess receptive vocabulary. Data were analyzed using SPSS 25.0, with descriptive statistics, independent t-tests, and chi-square tests applied. P < 0.05 was considered statistically significant. Results: The mean PPVT-4 score for the 36–48 months group was 80.1 ± 10.2, while for the 49–60 months group, it was 90.3 ± 10.5 (p < 0.001). Only 33.5% of older children had age-appropriate vocabulary, compared to 79.5% of younger children. Gender differences were not significant (p = 0.288). Conclusion: Preschool children exhibited significant delays in receptive English vocabulary, particularly in older age groups. Early language interventions are recommended to improve vocabulary acquisition in bilingual settings.